The Use of Internet and its Effect on Decision Making Among Urology Patient: Survey Study - Alenezi, Saad; Alfahad, Mohammad; Aldousari, Saad; Al-shaiji, Tariq; Salem, Shady (International Journal of Innovative Research in Medical Science, 2023)
Introduction: Internet access is more than 90% in gulf countries, patients more often search the internet for their disease conditions. Very few published literatures regarding frequency sources and their impact on patients’ decision. Methods: We prepared a questionnaire inquiring about internet use, sources and effect on patient’s medical decision in tertiary general hospitals and specialized urology center. Results: We received 425 responses to the questionnaire over 3 months period. With 30% response among patients in outpatient department. Mean age was 43 ± 16.3 years, 325 males (76%) and 100 female (24%) responders. 266 (62.6%) patients had college degree and 159 (37.4%) had high school or lower education. 396 patients have internet access (91.6%). 303 (70%) searched for their condition. Google was the most common search tool 299 (69%). 137 (31.8%) patients reported that the internet affected their decision. for medical information 148 (34.9%) patients followed doctors personal pages 144 (33.9%), chose official government websites and 95 (22.4%) used medical websites. Conclusion: Internet use is reality, most of the patients in our region utilize it to learn about their diseases. Thirty percent reported it affected their treatment choice.